EFFECTIVENESS OF M-CHAT IN SCREENING AUTISM IN CHILDREN WITH SPECIAL NEEDS AT SLB FISABILILLAH MUARO PANEH, SOLOK REGENCY - Lailatul Husna; Rahmahtrisilvia; M. Sukron; Rezki Vidora; Wulan Hariani; Tria Ardianti (STMIK Indonesia Banda Aceh, 2026)
Autism is a complex neurological development disorder that affects communication skills , social interactions , and children's behavior . Early detection is the key to providing appropriate and effective interventions . This study aims to describe the effectiveness of using the Modified Checklist for Autism in Toddlers (M-CHAT) instrument as an autism screening tool in children with special needs at the Fisabilillah Special Needs School (SLB). The research method used is descriptive qualitative with a case study approach . The subject of the study was a 9 -year- old 11- month- old student who participated in the educational program at the Fisabilillah Special Needs School. Data were collected through structured interviews using the M-CHAT instrument consisting of 23 question items, direct observation , and documentation review. The results of the analysis showed that the subject showed eye contact response patterns , responses to names, and social imitation abilities. These findings identify the need for further evaluation by experts . The M-CHAT instrument has proven effective as an initial screening tool that is practical, easy to apply by educators, and able to systematically identify indicators of autistic behavior . in the SLB environment .